Predictors of Outcome in Patients with Pulmonary Hypertension Undergoing Mitral and Tricuspid Valve Surgery - Ee Phui Kew; Vincenzo Caruso; Julia Grapsa; Paolo Bosco; Gianluca Lucchese (Medicina, 2023)
Background and Objectives: Pulmonary hypertension (PH) secondary to left-sided valvular heart disease is associated with poor cardiac surgical outcome compared with patients without PH. Our objective was to investigate the prognostic factors of surgical outcome in patients with PH undergoing mitral valve (MV) and tricuspid valve (TV) surgery, in order to risk stratify their management. Materials and Methods: This is a retrospective observational study on patients with PH who underwent MV and TV surgery from 2011 to 2019. The primary outcome was all-cause mortality. The secondary outcomes were post-op respiratory and renal complications, length of intensive care unit stay and length of hospital stay. Results: Seventy-six patients were included in this study. The all-cause mortality was 13% (n = 10), with mean survival of 92.6 months. Among the patients, 9.2% (n = 7) had post-op renal failure requiring renal replacement therapy and 6.6% (n = 5) had post-op respiratory failure requiring intubation. Univariate analysis demonstrated that pre-operative left ventricular ejection fraction (LVEF), peak systolic tissue velocity at the tricuspid annulus (S’) and etiology of MV disease were associated with respiratory and renal failure. Tricuspid annular plane systolic excursion (TAPSE) was associated with respiratory failure only. S’, type of operation, LVEF, urgency of surgery, and etiology of MV disease were found to be predictive of mortality. After excluding redo mitral surgery, all statistically significant findings remain unchanged, with the addition of right ventricular (RV) size being associated with respiratory failure. In the subgroup analysis of routine cases (n = 56), patients with primary mitral regurgitation who underwent mitral valve repair had better survival outcome. Conclusions: Urgency of surgery, etiology of MV disease, type of operation (replacement or repair), S’ and pre-op LVEF are prognostic indicators in this small cohort of patients with PH undergoing MV and TV surgery. A larger prospective study is warranted to validate our findings.